Multiple and distinct strategies of yeast SNAREs to confer the specificity of membrane fusion - Furukawa, Noriko (Nature Publishing Group, 2014)
Trans-QabcR-SNARE pairing on opposing membranes is crucial for eukaryotic membrane fusion, but how selective pairs of Qabc- and R-SNARE proteins regulate membrane fusion specificity remains elusive. Here, we studied 14 purified full-length SNAREs that function in yeast endoplasmic reticulum (ER)-Golgi, intra-Golgi, endosomal, and vacuolar transport by comprehensively testing cis-QabcR-SNARE assembly and fusogenicity of reconstituted SNARE proteoliposomes. Strikingly, the cognate ER-Golgi and intra-Golgi SNARE-complex assemblies were highly stringent, whereas endosomal and vacuolar SNAREs assembled rather promiscuously into the non-cognate mixed complexes. However, these patterns of cis-SNARE assemblies cannot solely explain their potency to be fusogenic via trans-SNARE pairing: Only the vacuolar 3Q-SNARE combination is fusogenic in the absence of additional components; endosomal SNARE-dependent fusogenicity requires membrane-tethering factors; and ER-Golgi SNAREs can be fusogenic by synergistic actions of tethering factors and the cognate Sec1/Munc18-family protein Sly1p. Thus, our findings uncover multiple and distinct strategies of SNAREs to directly mediate fusion specificity.